2009
DOI: 10.1016/j.ajhg.2009.01.023
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-wide Analysis Identifies Genetic Variants in the RELN Gene Associated with Otosclerosis

Abstract: Otosclerosis is a common form of progressive hearing loss, characterized by abnormal bone remodeling in the otic capsule. The etiology of the disease is largely unknown, and both environmental and genetic factors have been implicated. To identify genetic factors involved in otosclerosis, we used a case-control discovery group to complete a genome-wide association (GWA) study with 555,000 single-nucleotide polymorphisms (SNPs), utilizing pooled DNA samples. By individual genotyping of the top 250 SNPs in a step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
99
2
9

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(120 citation statements)
references
References 41 publications
10
99
2
9
Order By: Relevance
“…In the Caucasian population, it has been observed that each minor allele (C) at rs3914132 in RELN gene is acting as a protective allele and decreases the risk of otosclerosis by 1.54 times. In the same study, expression of reelin was also detected in human stapedial footplate samples without OTSC (Schrauwen et al, 2009a). The exact role of RELN in the bone remodeling of the otic capsule is not yet known.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…In the Caucasian population, it has been observed that each minor allele (C) at rs3914132 in RELN gene is acting as a protective allele and decreases the risk of otosclerosis by 1.54 times. In the same study, expression of reelin was also detected in human stapedial footplate samples without OTSC (Schrauwen et al, 2009a). The exact role of RELN in the bone remodeling of the otic capsule is not yet known.…”
Section: Discussionmentioning
confidence: 51%
“…It is not clear whether the reelin acts as such in the otic capsule of the ear. Although reelin has been shown to be expressed in the human stapedial footplate samples, human inner ear and mouse inner ear, the exact role in pathogenesis of OTSC is not yet known (Schrauwen et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several association studies reveal the implication of COL1A1 (McKenna et al, 1998), TGFB1 (Thys et al, 2007a), BMP2, BMP4 , ACE and AGT (Imauchi et al, 2008) in the development of the disease, although the evidence for association with COL1A1, ACE and AGT is controversial (Rodriguez et al, 2004;Schrauwen et al, 2009c). A recent genome wide association study (GWAS) in a population of European origin identified two new regions associated with otosclerosis (Schrauwen et al, 2009b). The first region, on chr7q22.1, is located in the Reelin (RELN) gene.…”
Section: Introductionmentioning
confidence: 99%
“…For the complex form of otosclerosis, several association studies were performed to identify genes. [9][10][11][12] Many different hypotheses for the etiology of otosclerosis have been proposed, including several theories involving a role for the immune system. It has been suggested that disease pathology can be induced by an autoimmune reaction to type II collagen present in embryonic cartilaginous remnants in the endochondral layer of the otic capsule.…”
Section: Introductionmentioning
confidence: 99%